Chagas disease is related to structural changes of the gut microbiota in adults with chronic infection (TRIPOBIOME Study) - Pérez-Molina, José A.; Crespillo-Andújar, Clara; Trigo, Elena; Chamorro, Sandra; Arsuaga, Marta; Olavarrieta, Leticia; Navia, Beatriz; Martín, Oihane; Monge-Maillo, Begoña; Norman, Francesca F.; Lanza, Val F.; Serrano-Villar, Sergio (PLOS Neglected Tropical Diseases, 2023)
Background The implications of the gut microbial communities in the immune response against parasites and gut motility could explain the differences in clinical manifestations and treatment responses found in patients with chronic Chagas disease. Methodology/Principal findings In this pilot prospective cross-sectional study, we included 80 participants: 29 with indeterminate CD (ICD), 16 with cardiac CD (CCD), 15 with digestive CD (DCD), and 20 controls without CD. Stool was collected at the baseline visit and faecal microbial community structure DNA was analyzed by whole genome sequencing. We also performed a comprehensive dietary analysis. Ninety per cent (72/80) of subjects were of Bolivian origin with a median age of 47 years (IQR 39–54) and 48.3% (29/60) had received benznidazole treatment. There were no substantial differences in dietary habits between patients with CD and controls. We identified that the presence or absence of CD explained 5% of the observed microbiota variability. Subjects with CD exhibited consistent enrichment of Parabacteroides spp, while for Enterococcus hirae, Lactobacillus buchneri and Megamonas spp, the effect was less clear once excluded the outliers values. Sex, type of visceral involvement and previous treatment with benznidazole did not appear to have a confounding effect on gut microbiota structure. We also found that patients with DCD showed consistent Prevotella spp enrichment. Conclusions We found a detectable effect of Chagas disease on overall microbiota structure with several potential disease biomarkers, which warrants further research in this field. The analysis of bacterial diversity could prove to be a viable target to improve the prognosis of this prevalent and neglected disease.